Epidemiological and clinical aspects of scorpionism by Tityus trivittatus in Argentina - de Roodt, Adolfo Rafael (2003)
This is a descriptive study of epidemiological and clinical aspects of stings caused by the scorpion Tityus trivittatus in Argentina. We analyzed 511 cases recorded from different health centers in 22 provinces. Most accidents took place during the period November-April (76%), in or nearby houses (86%). Over 50% of the accidents involved children and teenagers. Envenomation by T. trivittatus was mainly characterized by local symptoms: pain (85%), edema (26.6%), burning sensation (24.7%), erythema (20.7%), local hyperthermia (13.1%), paresthesia (9.8%) and general manifestations such as vomiting (25%), paleness (18.8%), headache (11.4%) and sweating (8.2%). Neurological, cardiovascular and respiratory disorders were uncommon. Almost 90% of the injured people got treated with specific antivenom within 2 h, 6% were treated 2-h after the accident and only 2 people were treated 12 or more hours after being stung. The global mortality recorded was 6 per 1000 cases. Scorpionism in Argentina is a public health problem under control due to the relatively low incidence and the accessibility of specific antivenom.